SIMULASI MONTE CARLO UNTUK MENENTUKAN KEANDALAN PADA BAGIAN BOILER DI PEMBANGKIT LISTRIK BERBASIS BATUBARA - Iing Pamungkas; Heri Tri Irawan; Arhami Arhami; Muhammad Dirhamsyah (Universitas Teuku Umar, 2018)
PT. PLN (Persero) currently uses a lot of coal-based power plants or Steam Power Plants (PLTU) in carrying out its operational activities. Aceh Province has a PLTU located in Nagan Raya Regency and is owned by PT. PLN (Persero). The Nagan Raya power plant has two generating units with an installed capacity of 2x110 Megawatts. The highest frequency of interference or damage experienced by the boiler section and this is very influential on the Nagan Raya PLTU production system. Performance evaluation in terms of reliability is needed to minimize interference or damage. The purpose of this study is to determine the level of reliability using Monte Carlo simulations on each important component of the boiler section. Monte Carlo simulations will be used to predict the time between failure or time to failure (TTF) and time to repair (TTR) so that the level of reliability can be predicted in the future. Monte Carlo simulations basically produce uniformly distributed random numbers (0.1) and then convert them into non-uniform distributions using the inverse transformation method. Monte Carlo simulation results on eight critical components in the boiler section obtained time to failure (TTF) obtained were 260 hours to 1312 hours with a reliability value of 30% to 42%. While the time to repair (TTR) is 1,57 hours to 2,26 hours with a reliability value of 22% to 41%.